Analisis Risiko Kecelakaan Kerja Menggunakan Metode HIRARC dan Fault Tree Analysis (FTA) pada Proses Progressive dan Welding di PT X - Dominicus Rivaldi; Ferida Yuamita (KAMPUS AKADEMIK PUBLISING, 2026)
Occupational Occupational Safety and Health (OSH) plays an important role in preventing workplace accidents and maintaining productivity in manufacturing industries. PT X is a metal manufacturing company with high-risk activities in the Progressive and Welding processes. In 2025, the company recorded six workplace accidents, indicating the need for systematic risk evaluation. This study aims to identify workplace hazards, assess risk levels, analyze the root causes of accidents, and propose appropriate control measures. A descriptive quantitative approach was employed using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method integrated with Fault Tree Analysis (FTA). Data were collected through observations, interviews, and company documentation. The HIRARC results identified workplace hazards with different risk levels, while FTA revealed that accidents were primarily caused by human, machine, method, material, and environmental factors. Based on these findings, risk control recommendations were developed according to the hierarchy of controls, including engineering controls, administrative controls, the proper use of personal protective equipment (PPE), and improved safety training. These recommendations are expected to reduce workplace accident risks and enhance the implementation of Occupational Safety and Health (OSH) in the company.